Quantificando a centralidade urbana: Uma proposta de índice simples e comparaç\~ao internaciona - Rafael Henrique Moraes Pereira; Vanessa Nadalin; Leonardo Monasterio; Pedro Henrique Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This study introduces a new measure of urban centrality. It identifies distinct urban structures from different spatial patterns of jobs and resident population. The proposed urban centrality index constitutes an extension to the spatial separation index (MIDELFART-KNARVIK et al., 2000). It is suggested that urban structure should be more accurately analyzed when considering a centrality scale (varying from extreme monocentricity to extreme polycentricity) rather than being considered as a binary variable (monocentric or polycentric). The proposed index controls for differences in size and shape of the geographic areas for which data is available and can be calculated using different variables such as employment and population densities or trip generation rates. The properties of the index are illustrated in simulated artificial data sets. Simulation results for hypothesized urban forms are compared to other similar measures proposed by previous literature. The index is then applied to the urban structure of four different Metropolitan Areas: Pittsburgh and Los Angeles in the United States, S\~ao Paulo in Brazil and Paris, France, comparing to other traditional spatial agglomeration measures such as global and local Moran's I, and density gradients estimations.
Keywords: R10; R12; R14; N90; 330